IMPACT OF MATERIALS MANAGEMENT PRACTICES IN THE NIGERIAN BUILDING CONSTRUCTION INDUSTRY - Idowu ALBERT; Winston SHAKANTU; Kabir IBRAHIM (Journal of Construction Project Management and Innovation)
Construction materials are a major cost component in any construction project. A factor that affects the performance of construction projects to a large extent is the poor management of materials during site activities. The research centered on impact of materials management practices in the Nigerian construction industry. This study assessed the impact of materials management with emphasis on building projects. Data were collected with the aid of questionnaires administered to professionals in construction sites. The data generated were analysed using descriptive statistics. The research findings indicate that the main impacts of effective materials management practices are reduced cost of materials, good quality control, better field material control, better handling of materials, adequate storage of materials on site, improvements in productivity and completion of project on time. Based on the findings, it was concluded effective materials management practices improve the overall handling of materials for more efficiency and effectiveness on the construction site. The paper recommends that there should be proper planning of material management practices right from the inception of project execution and should also be practiced on all sites and by all categories of construction industry, whether large, medium or small so as to ensure timely project execution and standard work delivery within reasonable cost, time and quality.